UPAYA DEWAN PIMPINAN DAERAH PARTAI NASIONAL DEMOKRAT PEKANBARU DALAM MEMENUHI SYARAT VERIFIKASI PARTAI POLITIK TAHUN 2012 - Ferry Farisca; Hery Suryadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
NasDem Party is the only party that qualify as new participants in the election of 2014. NasDem That means the party is entitled to vote for the first time in 2014. Expansion is carried out by the party structure NasDem Pekanbaru regarding structuring the management of the party NasDem Pekanbaru an effort to achieve party verification politics in the city of Pekanbaru.This research is a descriptive study using a qualitative approach as a tool of analysis. This research was conducted in Ujung Batu sub-district, Rokan Hulu. This research was using interviews with key informants as information objects that aim to achieve the goal in order to get information in this research. Data used of this research is primary data and secondary data obtained through observation and interviews with key informants in this research.NasDem Party of Pekanbaru in expanding the network as attempts to institutionalize political party or effort, there are some efforts that do include: 1) Systemic Dimension: O250 is an information technology-based systems carried out by the NasDem Party of Pekanbaru in expanding his political network in this case as well as a tool recruiting members. O250 is an abbreviation of Operation 250. 2) Dimensions of Identity Value: Performance of the Governing Council of the Regional Leadership NasDem Party Pekanbaru also contribute to the expansion of the network, as well as to the candidates also sought in terms of activities, among others, by socializing NasDem Party Pekanbaru coupled with campaign himself as a political candidate. 3) Dimensions of Autonomy: wing party or organization supporting the existence of the party as a party that aims to support the dissemination of even recruiting Party members NasDem Pekanbaru. 4) Dimension Reification: The mass media as a supporting party or as a means of reinforcing NasDem identity Nasdem Party Pekanbaru. Print media that tend to favor the attempt to socialize as well as NasDem Party of Pekanbaru, this is very helpful step NasDem capital city of Pekanbaru with introduction and news through the media.Keywords: Efforts, National Democratic Party, Political Party Verification